Factors Affecting Adjuvant Therapy in Stage III Pancreatic Cancer—Analysis of the National Cancer Database. (30th August 2017) - Krishnan, Mridula; Ahmed, Aabra; Walters, Ryan W; Silberstein, Peter T
Background: Adjuvant therapy after curative resection is associated with survival benefit in stage III pancreatic cancer. We analyzed the factors affecting the outcome of adjuvant therapy in stage III pancreatic cancer and compared overall survival with different modalities of adjuvant treatment. Methods: This is a retrospective study of patients with stage III pancreatic cancer listed in the National Cancer Database (NCDB) who were diagnosed between 2004 and 2012. Patients were stratified based on adjuvant therapy they received. Unadjusted Kaplan-Meier and multivariable Cox regression analysis were performed. Results: We analyzed a cohort included 1731 patients who were recipients of adjuvant therapy for stage III pancreatic cancer within the limits of our database. Patients who received adjuvant chemoradiation had the longest postdiagnosis survival time, followed by patients who received adjuvant chemotherapy, and finally patients who received no adjuvant therapy. On multivariate analysis, advancing age and patients with Medicaid had worse survival, whereas Spanish origin and lower Charlson comorbidity score had better survival. Conclusions: Our study is the largest trial using the NCDB addressing the effects of adjuvant therapy specifically in stage III pancreatic cancer. Within the limits of our study, survival benefit with adjuvant therapy was more apparent with longer duration from date of diagnosis.